Geopolitikkens geografi - Larsen, Henrik Gutzon (Politik, 2011)
Over the past decades, a ‘neoclassical geopolitics’ has emerged in and beyond the field of International Relations. This diverse practice reproduces many of the problems that characterised classical geopolitics, notably an excessive tendency to explain politics on the basis of ostensibly permanent geographical factors. As a contribution to the interdisciplinary dialogue between International Relations and (Political) Geography, this article outlines the history of classical geopolitical reasoning and some problems that relate to this tradition. The contemporary perspective of ‘critical geopolitics’ is introduced as a radically different alternative. But the core problem of classical as well as neoclassical geopolitics is a superficial understanding of geographical space, which all too easily results in geographical determinism. For this reason, particular emphasis is placed on different conceptions of space. It is argued that rather than looking to classical geopolitics with its scientific and ultimately also politically problematic notions of geography, analyses of international and global politics is better served by adopting a relational approach to geography, which stresses the geographical as dialectically related to the social and the historical.